Evaluating the Potential of Legumes to Mitigate N2O Emissions From Permanent Grassland Using Process‐Based Models. Issue 12 (26th November 2020) - Fuchs, Kathrin; Merbold, Lutz; Buchmann, Nina; Bellocchi, Gianni; Bindi, Marco; Brilli, Lorenzo; Conant, Richard T.; Dorich, Christopher D.; Ehrhardt, Fiona; Fitton, Nuala; Grace, Peter; Klumpp, Katja; et al.
Abstract: A potential strategy for mitigating nitrous oxide (N2 O) emissions from permanent grasslands is the partial substitution of fertilizer nitrogen (Nfert ) with symbiotically fixed nitrogen (Nsymb ) from legumes. The input of Nsymb reduces the energy costs of producing fertilizer and provides a supply of nitrogen (N) for plants that is more synchronous to plant demand than occasional fertilizer applications. Legumes have been promoted as a potential N2 O mitigation strategy for grasslands, but evidence to support their efficacy is limited, partly due to the difficulty in conducting experiments across the large range of potential combinations of legume proportions and fertilizer N inputs. These experimental constraints can be overcome by biogeochemical models that can vary legume‐fertilizer combinations and subsequently aid the design of targeted experiments. Using two variants each of two biogeochemical models (APSIM and DayCent), we tested the N2 O mitigation potential and productivity of full factorial combinations of legume proportions and fertilizer rates for five temperate grassland sites across the globe. Both models showed that replacing fertilizer with legumes reduced N2 O emissions without reducing productivity across a broad range of legume‐fertilizer combinations. Although the models were consistent with the relative changes of N2 O emissions compared to the baseline scenario (200 kg N ha −1  yr −1 ; no legumes), they predicted different levels of absolute N2 O emissions and thus also of absolute N2 O emission reductions; both were greater in DayCent than in APSIM. We recommend confirming these results with experimental studies assessing the effect of clover proportions in the range 30–50% and ≤150 kg N ha −1  yr −1 input as these were identified as best‐bet climate smart agricultural practices. Key Points: A partial substitution of fertilizer nitrogen with symbiotically fixed nitrogen could mitigate nitrous oxide (N2 O) emissions in grasslands by around 130 Gg yr −1 Experimentally testing this mitigation option is challenging so modeling offers means to identify the optimum legume/fertilizer combination The models showed that net benefits to N2 O mitigation and yield can be achieved across a wide range of legume/fertilizer combinations